The notion of a woman in the work of Stefan the First-Crowned - Đekić Đorđe N.; Zarković Božidar V. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2020)
The most frequently mentioned woman in the literary work of Stefan the First-Crowned is the Blessed Virgin, a God pleasing role model whose pursuit leads to the salvation of the soul. She was also a role model to his father, Stefan Nemanja. In addition, she was at the same time the most common example of a role model of mother followed by all mothers, as well as his mother Ana and his grandmother. His father's mother was mentioned but remained nameless. Of the other roles of a woman, in the centre of his attention was the wife of a husband. The context in which he mentioned her was the matrimonial law-penalties for unlawful marriage, unlawful dissolution of marriage, an adulterous woman, and forbidden marriage with sister-in-law. However, no mention was made of the obligations of parents, of a mother towards children, or of the adult children towards mothers. It must be noted that he did not talk much about a woman as a mother, though he did provide some information. It was fragmentary information about the mother-in-law, the widow, but there is no information about a woman-sister, woman-daughter, which is a striking testimony that he was not interested in these aspects of a woman. Apparently, he was only interested in a woman as a God-pleasing role model, among other things, God-pleasing mothers also in the sense of regulating marital relations.